The Scope And Challenges Of Entrepreneurial Education In Developing Entrepreneurial Skills Of University Students In Uzbekistan (Texas Journal of Philology, Culture and History, 2024)
Till the early 1970s, entrepreneurship was not considered a significant asset. It has now been incorporated into the education system, including the greatest teaching practices provided at elite universities such as Harvard(Ubogu, 2020). This is because the skills and knowledge required by today's and tomorrow's jobs are evolving. Education systems at certain levels must react and adapt to the new problems and challenges(Grecu and Denes, 2017a). Today, most educational institutions are becoming cognizant of the need to incorporate entrepreneurial skills into their curriculum(Mahmood et al., 2020). However, implementing entrepreneurial education is not an easy process and has a lot of challenges and barriers. This study`s goal is to find out the challenges and barriers in entrepreneurial education in Uzbekistan in the process of developing university students` abilities and skills which will be useful for future researchers, government, and policymakers who want to work in promoting entrepreneurial education in the country. Moreover, the study investigates the existence of entrepreneurial education in traditional universities in the Republic. A quantitative data collection method will be used to collect data and information from the two Universities (Team University and Westminster International University) in Tashkent, Uzbekistan while providing two separate questionnaires containing open-ended and closed-ended questions for the students and lecturers of both Universities. The final result reveals the challenges of entrepreneurial education from the perspective of students and lecturers at the university level in Uzbekistan. Outdated curricula and education system, unqualified lecturers, and wrong attitudes towards entrepreneurial education are among the main challenges. The findings suggest that at some level entrepreneurial education is practiced by the traditional universities in Uzbekistan although to confirm it a larger sample of people needs to be surveyed throughout Uzbekistan by future researchers. According to the responses by the students, most of them believed that the courses they had taken were effective and have had motivated them to start their business in the future. Most of the students and lecturers surveyed were optimistic about the future growth of the entrepreneurial education in the Republic while suggesting more attention and investment to be made in order to accelerate the speed of the development and progress